2019
DOI: 10.3390/molecules24061085
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Gastroprotective, Cytotoxic Activities and UHPLC PDA-Q Orbitrap Mass Spectrometry Identification of Metabolites in Baccharis grisebachii Decoction

Abstract: The decoction of the local plant Baccharis grisebachii is used as a digestive, gastroprotective, external cicatrizing agent and antiseptic in Argentine. A lyophilized decoction (BLD) from the aerial parts of this plant was evaluated regarding its anti-ulcer, antioxidant and cytotoxic activities and the bioactivities were supported by UHPLC-MS metabolome fingerprinting which revealed the presence of several small bioactive compounds. The antioxidant properties were evaluated by DPPH, TEAC, FRAP and lipoperoxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 66 publications
2
18
0
3
Order By: Relevance
“…The orange-yellow resin from Z.punctata (ZpRe) displayed a stronger DPPH scavenging activity with an EIC 50 25.72 µg/mL, as well as an outstanding inhibition of lipid peroxidation in erythrocytes (70% percent at 100 µg ZpRe/mL), this was comparable to the value shown by the reference compound catechin (74% at 100µg/mL) ( Table 2) and to the values shown recently by others Andean species [14,15,18]. Phenolic antioxidant compounds acting as free radical scavengers can delay or inhibit lipid oxidation processes.…”
Section: Total Phenolic and Flavonoid Contents And Antioxidant And Asupporting
confidence: 65%
See 1 more Smart Citation
“…The orange-yellow resin from Z.punctata (ZpRe) displayed a stronger DPPH scavenging activity with an EIC 50 25.72 µg/mL, as well as an outstanding inhibition of lipid peroxidation in erythrocytes (70% percent at 100 µg ZpRe/mL), this was comparable to the value shown by the reference compound catechin (74% at 100µg/mL) ( Table 2) and to the values shown recently by others Andean species [14,15,18]. Phenolic antioxidant compounds acting as free radical scavengers can delay or inhibit lipid oxidation processes.…”
Section: Total Phenolic and Flavonoid Contents And Antioxidant And Asupporting
confidence: 65%
“…The ability of the ZpReresin at three concentrations (100, 250, and 500 µg/mL) and of catechin at a single concentration (100 µg/mL) to inhibit lipoperoxidation in erythrocytes (LP), induced by tert-Butyl hydroperoxide, was determined. Relevant technical aspects of the trial have been reported recently in detail [15,18]. The values obtained are expressed as percentages of lipid oxidation inhibition.…”
Section: Lipid Peroxidation In Erythrocytesmentioning
confidence: 99%
“…Rhaponticin was also detected in other plants such as Trigonella foenum-graecum L. (fenugreek) (He et al 2016;Li et al 2018), Guibourtia tessmannii (Harms) J. Leonard (Nyemba et al 1995), Stuhlmannia moavi Taub. (Liu et al 2013), Eucalyptus rubida H. Deane & Maiden (Etoh et al 1990) and Baccharis grisebachii Hieron (Gómez et al 2019).…”
Section: Sources Of Rhaponticin and Its Content In Plantderived Prepamentioning
confidence: 99%
“…Some Baccharis species are used in folk medicine, including for spasmolytic, diuretic, and analgesic purposes and for the treatment of ulcers, fever, gastrointestinal illnesses, diabetes, and microbial infections [4,5,6]. Previous phytochemical studies of this genus have reported several classes of natural products, such as chlorogenic acid derivatives [4,7,8,9,10], terpenoids [11,12,13,14,15,16,17,18,19,20,21,22], especially diterpenes with dozens of isolated compounds from Baccharis [4,5,17,18,19,20,21,22], and flavonoids from flavone, flavanone, and flavonol types [4,5,21,22,23,24,25,26]. Furthermore, it has also been described as having diverse biological activities including antimicrobial [4,5,6,14,15], antiviral [4,5,6], antiprotozoal [9,24,25], anti-inflammatory [10,13], cytotoxic [4,5,6,23], and antioxidant [7,13,14,15,22,…”
Section: Introductionmentioning
confidence: 99%